Comparison of intravenous or intravesical cidofovir in the treatment of BK polyomavirus‐associated hemorrhagic cystitis following adult allogeneic stem cell transplantation—A systematic review. Issue 4 (21st June 2018) - Schneidewind, Laila; Neumann, Thomas; Schmidt, Christian Andreas; Krüger, William
Abstract: Introduction: BK polyomavirus can lead to hemorrhagic cystitis (BKPyV‐HC) in allogeneic stem cell transplantation and therefore to increased morbidity. No causal therapy has been established yet. Cidofovir (CDV) is a nucleotide analog of cytosine that is active against various DNA viruses and it has been described for therapy of BKPyV‐HC using 2 admission routes: intravenous and intravesical. Methods: We performed a systematic review regarding the comparison of intravenous or intravesical cidofovir in the treatment of BKPyV‐HC following adult allogeneic stem cell transplantation. Since there is a lack of randomized controlled trials, we considered all kinds of studies for this review. Due to heterogeneity of the data, we were not able to perform a meta‐analysis, so the results are shown descriptively. Results: The literature search for primary studies yielded 232 results. Finally, 9 studies where considered which included a total of 189 adult patients with BKPyV‐HC after allogeneic stem cell transplantation. We could only identify retrospective studies for this review. A total of 172 patients received intravenous CDV, 17 patients received intravesical CDV, and 2 patients received CDV in both admission routes. In 68.0% of the cases, a complete response for intravenous CDV was documented and in 88.2% for intravesical CDV. Interestingly, no kidney toxicity was mentioned in intravesical CDV. 9.3% of the intravenously treated patients had renal failure. Conclusion: There is only weak evidence for the use of CDV. The intravesical admission route should be further investigated because of a good toxicity profile.